Digital Campaign Strategies to Reduce Schizophrenia Stigma Among Adolescents: A Review - Yuli Solihati; Ruslan Majid; Syawal Kamiluddin Saptaputra; Asriati; Jumakil; Hilda Harun (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Schizophrenia is a severe mental disorder often accompanied by negative stigma, especially among adolescents. This stigma remains a major barrier preventing individuals from seeking professional help. In the digital era, social media and online platforms offer new opportunities to deliver mental health education and campaigns that are accessible and engaging for young audiences. Objective: This study aims to identify and analyze effective digital campaign strategies to reduce stigma toward schizophrenia among adolescents based on recent literature findings. Method: This research employed a Systematic Literature Review (SLR) guided by the PRISMA framework. Articles were collected from databases including Google Scholar, PubMed, Scopus, ResearchGate, and ScienceDirect within the 2020–2025 period. Data were analyzed descriptively to determine patterns and the effectiveness of digital campaign strategies. Results: The review found that the use of digital media such as motion graphics, short videos, infographics, and storytelling on platforms like Instagram, TikTok, and YouTube effectively increased knowledge, empathy, and reduced negative stereotypes toward individuals with schizophrenia. Approaches involving social contact and recovery stories were shown to have a significant positive impact on adolescents’ attitudes. Conclusion: Digital campaigns are a promising strategy to reduce schizophrenia-related stigma among adolescents. However, challenges such as digital addiction, misinformation, and disparities in media literacy need to be considered. Campaigns should be evidence-based and supervised by mental health professionals to ensure their effectiveness and safety in promoting mental health awareness.